2010
DOI: 10.1111/j.1752-4571.2009.00111.x
|View full text |Cite
|
Sign up to set email alerts
|

Do male and female black‐backed woodpeckers respond differently to gaps in habitat?

Abstract: We used population- and individual-based genetic approaches to assess barriers to movement in black-backed woodpeckers (Picoides arcticus), a fire-specialist that mainly occupies the boreal forest in North America. We tested if male and female woodpeckers exhibited the same movement patterns using both spatially implicit and explicit genetic analyses to define population structure and movement patterns of both sexes among populations. Three genetic groups were identified, a large, genetically continuous popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
34
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 87 publications
(165 reference statements)
1
34
0
Order By: Relevance
“…Pierson et al [17] concluded that the extent of the genetic distinction between these two populations was "similar to those documented among subspecies" in other birds occupying similar ranges. Pierson et al [17] did not collect genetic samples from the California population of black-backed woodpeckers.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Pierson et al [17] concluded that the extent of the genetic distinction between these two populations was "similar to those documented among subspecies" in other birds occupying similar ranges. Pierson et al [17] did not collect genetic samples from the California population of black-backed woodpeckers.…”
Section: Introductionmentioning
confidence: 99%
“…Pierson et al [17] concluded that the extent of the genetic distinction between these two populations was "similar to those documented among subspecies" in other birds occupying similar ranges. Pierson et al [17] did not collect genetic samples from the California population of black-backed woodpeckers. Further study is warranted to clarify the relationship of the population in California, which may also be disjunct to some degree with the eastern Oregon Cascades population, and is disjunct with other populations of the species.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As is expected given the isolation of the Black Hills, phylogenetic analyses have shown that these two forest-dependent squirrels (Kiesow 2008), as well as two woodpeckers (Black-backed Woodpecker, Picoides arcticus (Swainson, 1832): Pierson et al 2010; American Three-toed Woodpecker, Picoides dorsalis S.F. Baird, 1858: Ervin 2011, are morphologically and phylogenetically distinct from conspecifics found in more continuous boreomontane habitat.…”
Section: Introductionmentioning
confidence: 86%
“…Every woodpecker species has its preferences, according to their needs. For co-existing species -and different sexes -the interspeci fic, intraspecific and intrasexual competition is minimized by spatial segregation, so their realised niche differ from their fundamental niche (Peters & Grubb 1983, Pettersson 1983, Török & Csorba 1986, Székely 1987, Török 1990, Hogstad 1971, Olsson et al 1992, Osiejuk 1998, Stenberg & Hogstad 2004, Pierson et al 2010.…”
Section: Introductionmentioning
confidence: 97%